Lateral–Medial Dissociation in Orbitofrontal Cortex–Hypothalamus Connectivity - Hirose, Satoshi; Osada, Takahiro; Ogawa, Akitoshi; Tanaka, Masaki; Wada, Hiroyuki; Yoshizawa, Yasunori; Imai, Yoshio; Machida, Toru; Akahane, Masaaki; Shirouzu, Ichiro; Konishi, Seiki (Frontiers in Human Neuroscience, 2016)
The orbitofrontal cortex (OFC) is involved in cognitive functions, and is also closely related to autonomic functions. The OFC is densely connected with the hypothalamus, a heterogeneous structure controlling autonomic functions that can be divided into two major parts: the lateral and the medial. Resting-state functional connectivity has allowed us to parcellate the cerebral cortex into putative functional areas based on the changes in the spatial pattern of connectivity in the cerebral cortex when a seed point is moved from one voxel to another. In the present high spatial-resolution fMRI study, we investigate the connectivity-based organization of the OFC with reference to the hypothalamus. The OFC was parcellated using resting-state functional connectivity in an individual subject approach, and then the functional connectivity was examined between the parcellated areas in the OFC and the lateral/medial hypothalamus. We found a functional double dissociation in the OFC: the lateral OFC (the lateral orbital gyrus) was more likely connected with the lateral hypothalamus, whereas the medial OFC (the medial orbital and rectal gyri) was more likely connected with the medial hypothalamus. These results demonstrate the fundamental heterogeneity of the OFC, and suggest a potential neural basis of the OFC-hypothalamic functional interaction.